PENGARUH KOMUNIKASI,MOTIVASI, DAN DISIPLIN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA KANTOR POS CABANG PARE - Kurniawan, Muhamad Arief (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
In this research, the background is the results of research and the experience of researchers. That the factors that play a role in work productivity are communication, motivation and discipline. The research objective was to determine the effect of communication, motivation, discipline on employee work productivity. This research technique is to use quantitative techniques. The population in this study were all employees of the Pare branch of the post office. The sample used in this study was 40 people at the Pare branch post office. The sampling method used in this study was accidental sampling. The data analysis technique used in this study is multiple linear regression, t test, f test. The results of this study state that 1) communication has an effect on the work productivity of the Pare branch post office employees. 2) Motivation has a significant effect on the work productivity of the Pare branch post office employees. 3) Communication, motivation, discipline simultaneously affect the dependent variable, namely employee work productivity Keywords: Communication, Motivation, Discipline, Employee Productivity